THE RELATIONSHIP OF KONJO DIALECT AND LAKIUNG DIALECT OF MAKASSAR LANGUAGE: A DIALECTOLOGICAL APPROACH - Dian Astuti; Kaharuddin; Gusnawaty (Bajang Institute, 2022)
This study discusses the relationship, namely the differences and similarities between the Lakiung (LK) dialect and the Konjo (KJ) dialect Makassar language at the phonological and lexical level with a dialectological approach. This study was conducted to find phonological and lexical differences as well as inventories of the status of the language and dialect map in the Konjo dialect and the Lakiung dialect of the Makassar language. This research uses quantitative and qualitative methods. Data collection in this study used the capable method and the listening method. The source of the research data is field data and literature data obtained through research instruments in the form of basic vocabularies of Morrish Swadesh. The data were analyzed quantitatively (dialectometry) and qualitatively. The results of the analysis showed that in the calculation of the phonological dialectometry scale on fifteen meaning fields there were 90 different glosses with a percentage of 25.86%. It can be categorized as a language difference. The lexical dialectometry scale shows a difference of 95 glosses with a percentage of 27.29%. It is included in the category of no difference in language and dialect. Furthermore, the results of the dialectometry calculation of the overall difference were 185 glosses with a percentage of 53.16%. So the Lakiung dialect and the Konjo dialect are included in the category of dialect differences. The vocal phonemes in the Lakiung dialect and the Konjo dialect are the same, that is, there are five vocal phonemes each, namely /a/, /i/, /u/, /e/, and /o/. The consonant phonemes in the Konjo dialect and the Lakiung dialect are also the same, that is, both have eighteen consonants, namely /k/, /ɡ/, /ŋ/, /p/, /b/, /m/, /ʦ/, /ʤ/, /ɲ/, /t/, /d/, /n/, /j/, /r/, /l/, /w/, /s, and /h/.